1998
DOI: 10.1002/(sici)1521-3765(19980807)4:8<1398::aid-chem1398>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear Oxidative Addition of Hydrogen in Diamidonaphthalene‐Bridged Diiridium Complexes

Abstract: ) (7 a, 7 b), in which a molecule of hydrogen has been added to form a terminal and a bridging hydride. In the presence of NEt 3 , 7 a and 7 b isomerize into the symmetric complex 8 which presents a trans arrangement of the hydrides. Oxidation of complex 1 allows the preparation of the iridium(ii) species [Ir 2 (m-1,8-(NH) 2 naphth)(OSO 2 CF 3 ) 2 -(CO) 2 (PiPr 3 ) 2 ] (9). The triflate ligands of 9 can be replaced by tetrahydrothiophene or acetonitrile to give complexes 10 and 11, respectively. The acetonitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
8
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 61 publications
3
8
0
Order By: Relevance
“…The oxidation of these d 8 d 8 diiridium compounds, to species of d 6 d 8 or d 7 d 7 electronic configurations, gave dihydrogen-activating compounds. [5] Here we report that such an oxidation strategy also allows the transformation of nonreactive d 8 d 8 compounds into dinuclear CÀH activating species.…”
supporting
confidence: 73%
See 4 more Smart Citations
“…The oxidation of these d 8 d 8 diiridium compounds, to species of d 6 d 8 or d 7 d 7 electronic configurations, gave dihydrogen-activating compounds. [5] Here we report that such an oxidation strategy also allows the transformation of nonreactive d 8 d 8 compounds into dinuclear CÀH activating species.…”
supporting
confidence: 73%
“…[3] Homoleptic systems are of particular interest since these species may function as ™naked∫ metal atom reagents and are therefore valuable precursors for the general exploration of low-valent transition metal chemistry. [4] Except for the first reported homoleptic polyarene transition metal complex [Ru(C 10 H 8 ) 2 ] 2 (C 10 H 8 naphthalene), [5] all previous examples contained only early (Groups 4 ± 6) transition metals. [4] However, the existence of this cationic ruthenium species suggested that related neutral and anionic polyarene complexes of later transition metals should also be accessible.…”
Section: Dedicated To Professor Klaus Jonasmentioning
confidence: 99%
See 3 more Smart Citations